Achieving Logistics Performance in Military Environmental Dynamism: The Role of Organizational Capabilities - Abdul Rahman, Abdul Rahim; Ab. Hamid, Noor Raihan (International Journal of Supply Chain Management, 2019)
This study aims to understand the factors that influence the Malaysian Army logistics performance and the role of process capability. In addition, this study also attempts to examine the role of learning capability between the military environmental dynamism and process capability. It also attempt to include strategic logistics alliances on the relationship between the process capability and the Malaysian Army logistics performance. Since this study is also focusing on how organizational learning capability and process capability play a role in achieving logistics performance, a more comprehensive conceptual framework is required. This research therefore is expected to fill the research gap by developing a new theoretical conceptual model by tying up three theories including dynamic capability, organizational learning, and social exchange theories.